Photophysics of a Coumarin in Different Solvents: Use of Different Solvatochromic Models. (18th March 2014) - Maity, Banibrata; Chatterjee, Aninda; Seth, Debabrata
Abstract This study reported the photophysics of 7‐(diethylamino)coumarin‐3‐carboxylic acid N‐succinimidyl ester (7‐DCCAE) in different neat solvents of varying polarity using steady‐state absorption, fluorescence emission and picosecond time‐resolved spectroscopy. In nonpolar solvents, the dye molecule predominantly exists in nonpolar structure and exhibits very low value of nonradiative decay rate constant (knr), demonstrating the emission takes place from S1‐LE to S0 ground state. The fluorescence quantum yields, lifetime values of 7‐DCCAE in different solvents are rationalized on the basis of intramolecular charge transfer (ICT) followed by twisted intramolecular charge transfer state formation (TICT) as well as specific solute–solvent interactions. Several solvatochromic models (such as Lippert, Dimroth, Kamlet–Taft, Catalán 3P and Catalán 4P models) were used to analyze the solvatochromic shift of 7‐DCCAE in different solvents. The different empirical models show that the observed results are better correlate for nonchlorinated solvents and provide statistically significant best‐fit result. A comparison was done between comparatively new solvatochromic model (Catalán 3P and Catalán 4P model) with Kamlet–Taft model. The ground state structure of the said molecule was optimized by using Density Functional Theory (DFT).